Storytelling Based on Contextual Learning with Hand Puppets in Early Childhood Language Development: Metode Storytelling Berbasis Contextual Learning dengan Boneka Tangan pada Perkembangan Bahasa Anak Usia Dini - Rini, Sri Asung Sundari; Mahabbati, Aini (Universitas Muhammadiyah Sidoarjo, 2025)
General background: Early childhood is a critical stage for language development, yet children at risk of learning difficulties often struggle with vocabulary, sentence construction, and confidence. Specific background: Conventional teaching methods in kindergartens frequently fail to address these challenges, particularly for children with barriers in receptive and expressive language. Knowledge gap: Limited research explores how contextual storytelling integrated with concrete media can support inclusive language learning. Aims: This study examines the application of contextual storytelling using hand puppets in improving the language skills of group B kindergarten children at risk of learning difficulties. Results: Conducted through two cycles of classroom action research, findings revealed that children’s average language scores rose from 47.5 (pre-test) to 58.3 (Cycle I) and 72.7 (Cycle II), with mastery increasing from 0% to 75%. Both receptive skills (understanding stories) and expressive skills (retelling and sentence-making) improved. Novelty: The integration of contextual storytelling with multisensory media provided richer experiences than conventional methods. Implications: This approach supports inclusive education by offering practical strategies for teachers and policymakers to foster meaningful language learning in early childhood. Highlight Storytelling with contextual learning and hand puppets enriched children’s language skills Receptive and expressive language abilities developed progressively through two research cycles The study offers practical strategies for inclusive early childhood education Keywords Storytelling, Contextual Learning, Language Development, Early Childhood, Inclusive Education